The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1590/s0103-50532003000300002
|View full text |Cite
|
Sign up to set email alerts
|

Heterogenization of alkene epoxidation catalysts

Abstract: Este trabalho descreve nosso esforço em heterogeneizar catalisadores para epoxidação. Tanto o molibdênio ancorado quanto o engaiolado pelo método de sol-gel mostraram grande seletividade, mas possuem suas atividades fortemente reduzidas. Por outro lado, silicatos de molibdênio foram muito ativos e estáveis até a formação de diols na mistura reacional. Catalisadores heterogeneizados de rênio foram menos ativos, mas permitiram o uso do peróxido de hidrogênio anidro como oxidante. Contudo, o alto custo e a dificu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…Alternative strategies to improve MTO-catalyzed oxidations have made use of host-guest inclusion chemistry [74][75][76][77][78][79][80][81]. It was found that an urea/hydrogen peroxide (UHP) complex is a very effective oxidant in heterogeneous olefin epoxidations and silane oxidations catalyzed by MTO [74].…”
Section: Epoxidations With Heterogenized Mto As the Catalystmentioning
confidence: 99%
“…Alternative strategies to improve MTO-catalyzed oxidations have made use of host-guest inclusion chemistry [74][75][76][77][78][79][80][81]. It was found that an urea/hydrogen peroxide (UHP) complex is a very effective oxidant in heterogeneous olefin epoxidations and silane oxidations catalyzed by MTO [74].…”
Section: Epoxidations With Heterogenized Mto As the Catalystmentioning
confidence: 99%
“…dihydrocarvone [3,4] and 1,2-limonene oxide. Because the latter compound is easily prepared from naturally available limonene [5], the interest for direct syntheses of carvenone from 1,2-limonene oxide has been increasing [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. However, most of the related reports showed that the selectivity towards carvenone was not good as expected.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in the latter case problems are described to have occurred during the catalytic reactions, such as swelling or leaching of the active species in the organic solution phase. Another strategy for the confinement of metal centres in mesoporous silicates is the covalent attachment of organometallic or coordination compounds to form hybrid materials [39][40][41][42][43]. Recently, modified MCM-41 and MCM-48 materials were synthesized by grafting MoO 2 X 2 (X = Cl, Br) and CpMo-(CO) 3 Cl, the latter being quite efficient homogeneous epoxidation catalysts [23][24][25][26]43].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, modified MCM-41 and MCM-48 materials were synthesized by grafting MoO 2 X 2 (X = Cl, Br) and CpMo-(CO) 3 Cl, the latter being quite efficient homogeneous epoxidation catalysts [23][24][25][26]43]. Additionally, surfacefixed bidentate Lewis bases have been used to bind Mo(VI) complexes as described by Gonçalves et al [44][45][46][47][48] and, independently, by Thiel et al [49][50][51] Silylation using Me 3 SiCl to remove residual Si-OH groups, which was considered to be favourable for the catalytic reaction on the surface of the mesoporous material [39][40][41][42], reduced the catalyst leaching significantly [49][50][51].…”
Section: Introductionmentioning
confidence: 99%